The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5551/jat.40352
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Fluorescent Angioscopy for Molecular Imaging of Human Atherosclerotic Coronary Plaque

Abstract: Purpose of Review: In vivo imaging of the native substances, including lipoproteins, that comprise human atherosclerotic plaques is currently beyond the scope of any available imaging techniques. Color and near-infrared fluorescent angioscopy (CFA and NIRFA, respectively) systems have been recently developed for molecular imaging of lipoproteins within the human coronary arterial wall ex vivo and/or in vivo. The author reviews recent findings on lipoprotein deposition in human coronary plaques obtained by thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…52,55 Using fluorescent angioscopy, LPC has been detected ex vivo in coronary artery plaques. 56 These data were supported by Ménégaut et al, who reported ex vivo increased levels of 2-arachidonoyl-lysophosphatidylcholine in carotid atheroma plaques of diabetic patients. 57 In agreement with these report, we found LPC to be more abundant in atherosclerotic plaques compared with normal arterial tissues.…”
Section: Discussionmentioning
confidence: 57%
“…52,55 Using fluorescent angioscopy, LPC has been detected ex vivo in coronary artery plaques. 56 These data were supported by Ménégaut et al, who reported ex vivo increased levels of 2-arachidonoyl-lysophosphatidylcholine in carotid atheroma plaques of diabetic patients. 57 In agreement with these report, we found LPC to be more abundant in atherosclerotic plaques compared with normal arterial tissues.…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies have established that oxLDL accumulates steadily in both early-stage (growing) and mature-stage (yellow plaque without a necrotic core) human coronary plaques but that, in more advanced vulnerable plaques (yellow plaques with a necrotic core), this lipoprotein is removed either by metabolism or replacement with other substances, including cell debris ( 2 ). These in vivo data dovetail well with the early in vitro work, which showed that while oxLDL promotes macrophage growth and survival in a dose-dependent manner, beyond a certain lipid concentration, cell death ensues, albeit by an unknown mechanism ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis, a progressive disease of arterial blood vessels and the main underlying cause of stroke, myocardial infarction, and cardiac death ( 1 ), is initiated by the conversion of plaque macrophages to cholesterol-laden foam cells ( 2 ) in the arterial intima ( 3 ). In the early-stage atherosclerotic plaque, this transformation is induced by the uptake of both low density lipoprotein-cholesterol (LDL-C) and oxidized LDL (oxLDL) ( 2 , 4 ), which may serve a beneficial purpose ( 3 ); but unrestrained, the crucial function of plaque macrophages in resolving local inflammation is compromised, and the development of unstable, advanced lesions ensues ( 3 ). It has been shown that foamy macrophages are not only less effective in clearing apoptotic cells ( 5 ), they are also more prone to apoptosis ( 6 ), thus increasing secondary necrosis and the release of cellular components and lipids that ultimately form the necrotic core of advanced plaques.…”
Section: Introductionmentioning
confidence: 99%
“…The cardiac chambers and valves were examined by Uchida. 35,36) Cellular AS, dye-staining AS and molecular AS were developed and used clinically by Uchida et al, 37) Uchida, 38) Uchida et al, 39,40) Uchida and Maezawa, 41) Uchida et al, 42,43) Uchida, 44) Uchida et al, 45,46) Uchida, 22,47,48) Uchida et al, 49,50) Uchida, 51,52) Uchida and Uchida. 53)…”
Section: Percutaneous Angioscopy (As) Is a High Resolution Fiberopticmentioning
confidence: 99%
“…Using this angiomicroscope, foam cells in the disrupted plaque can be clearly discerned in patients. 37,38 a-2 [40][41][42][43]52) This technique may contribute to the understanding and evaluation of molecular targeted therapies of not only for coronary artery disease but also for aortic disease.…”
Section: Cellular Imaging Using Intravascular Microscopymentioning
confidence: 99%